Clinicopathological analysis of programmed cell death 1 and programmed cell death ligand 1 expression in the tumour microenvironments of diffuse large B cell lymphomas. Issue 7 (1st December 2015) - Kwon, Dohee; Kim, Sehui; Kim, Pil‐Jong; Go, Heounjeong; Nam, Soo Jeong; Paik, Jin Ho; Kim, Young A; Kim, Tae Min; Heo, Dae Seog; Kim, Chul Woo; Jeon, Yoon Kyung
Abstract : Aims: To investigate the clinicopathological characteristics of programmed cell death ligand 1 (PD‐L1) and programmed cell death 1 (PD‐1) expression in the tumour microenvironments of diffuse large B cell lymphoma (DLBCL). Methods and results: Tumour tissues from 126 DLBCL patients were immunostained for PD‐L1 and PD‐1. The expression of PD‐L1 by tumour cells and/or tumour‐infiltrating immune cells (mainly macrophages) was evaluated, and the number of tumour‐infiltrating PD‐1 + cells was assessed. PD‐L1 expression in tumour cells was observed in 61.1% of DLBCLs, with a weak intensity in 29.4%, moderate intensity in 21.4% and strong intensity in 10.3% of cases. Strong PD‐L1 expression in tumour cells was associated significantly with the presence of B symptoms (adjusted P = 0.005) and Epstein–Barr virus (EBV) infection (adjusted P = 0.015), and tended to be higher in activated B cell‐like immunophenotype (16.7%) than germinal centre B cell‐like immunophenotype (2.5%) (adjusted P = 0.271). DLBCLs with PD‐L1 expression in tumour cells/macrophages showed similar clinicopathological characteristics. The quantity of PD‐1 + tumour‐infiltrating lymphocytes correlated positively with the level of PD‐L1 expression in tumour cells ( P = 0.042) or in tumour cells/macrophages ( P = 0.03). Increased infiltration of PD‐1 + cells was associated with prolonged progression‐free survival ( P = 0.005) and overall survival ( P = 0.026) in DLBCL patients treated with rituximab‐cyclophosphamide, doxorubicin, vincristine, prednisone (R‐CHOP), whereas PD‐L1 expression had no prognostic significance. Conclusions: PD‐L1 and PD‐1 were expressed variably in DLBCLs by tumour cells and tumour‐infiltrating immune cells and might be potential therapeutic targets using PD‐1/PD‐L1 blockade.